Pelatihan Bisnis Online Produk Herbal SR12 Di Desa Bantarjati Kecamatan Kelapanunggal berdasarkan Prinsip Ekonomi Islam - Putri, Wulan Lismanda; Asri, Kholifatul Husna (Neolectura, 2023)
Islamic economic principles through online business training to SR12 product entrepreneurs in Klapanunggal sub-district, Bogor district. This research was conducted through observation, interviews and documentation. The object of this research is SR12 product business actors in Klapanunggal District, Bogor Regency. With the existence of a business training program through online media, it is hoped that it can 1) help increase people's income in Bantarjati Village, Bogor Regency, because it does not require a lot of capital so it can be accepted by the community at the same time, 2) increase understanding of Islamic economic principles in business, 3) can help Marketing SR12 herbal products is better known to many consumers, and 4) can help develop more attractive and innovative products. Based on research results, business training based on Islamic economic principles is very important to be implemented in various fields, especially SR12 products, especially after Covid-19. Business actors receive online business training by creating a TikTok or using TikTok social media. This training implements the principles of Islamic economics, namely 1) product transactions are permitted based on Islamic law, 2) transactions must be based on benefit and justice, and 3) no usury element. Online business makes it easy for SR12 product entrepreneurs to market products to various regions, therefore it is necessary to understand how to implement online business in accordance with Islamic business ethics.